Designation of a solar falling-film photochemical hybrid system for the decolorization of azo dyes. (15th April 2020) - Zhang, Wei; Chen, Miao; Zhang, Shaofeng; Wang, Yiping
Abstract: Photovoltaics (PV) cells are widely applied in solar water purification systems as major parts of the solar photochemical (SPC) reactor. However, when the PV cells is equipped with flow channels as a SPC reactor, the output power drops significantly. To promote the electrical efficiency of the PV cell, a novel hybrid system that integrated the solar falling-film photochemical reactor with PV cells (SFPC) is developed for dye decolorization. Different from conventional SPC reactors, the designation of SFPC took the uncovered PV cell as a main part of the falling-film reactor. To evaluate the proposed design, decolorization efficiency and PV performance were analyzed between the SFPC system and SPC system. The results showed that the optical transmittance of the SFPC system promoted 20.3% in comparison with the SPC system, which enhanced the dye decolorization efficiency. Additionally, compared to the SPC system, the short-circuit current (Isc) and the maximum output power (Pmax) of the SFPC PV cell were improved by 27.12% and 33.55% respectively, for the treatment of acid red 26. Meanwhile, the Isc and Pmax were increased by 33.88% and 43.4% respectively, when treating acid brown 14. The proposed SFPC system shows high potential for dye decolorization and electricity generation. Highlights: A solar falling-film photochemical system integrated photovoltaics (SFPC) was built. The light transmittance of SFPC raised 20.3% than solar photochemical system (SPC). The P max in the SFPC achieved big improvement than SPC. PV cells in the SFPC has lower working temperature due to the falling film.